Substitution of Yellow Pumpkin Flour ( Cucurbita Moschata) in the Manufacture of Steamed Sponge as A High-Fiber Snack - Hasibuan, Henni Adlini; Agustina, Dewi; Eliska, Eliska (Indonesian Journal of Global Health Research, 2024)
Yellow pumpkin has a very high fiber content. Fiber is very good when used in making a soft diet in maintaining health and can launch metabolism The use of yellow pumpkin as flour in making steamed sponges has not been done much research on its nutritional value and advantages. Yellow pumpkin can be processed into free gluteen flour so that it is safe for consumption by the public, facilitates storage and can increase selling value. One bakery product that allows to add or replace some of the flour is steamed sponge. With the creation of the innovation of steamed sponges, yellow pumpkin flour is expected to be a healthy snack high in fiber. This study aims to obtain organoleptic test results and fiber content from steamed sponges made from yellow pumpkin flour. The method used was a true experiment with the Posttest Only Control Group design, which was then analyzed descriptively. This research consists of three stages, namely product development, product acceptance testing by panelists, and fiber content testing at the Organic Chemistry laboratory of FMIPA University of North Sumatra. The results of organoleptic tests obtained a very liking level for color by 48.0%, very liking for aroma by 36.0%, liking texture by 44.0% and a very liking level for taste by 36.0%. The results of the fiber content test were obtained at 55.14% from the mass of 33.58 grams of steamed sponge yellow pumpkin flour. The conclusion that based on the overall results of organoleptic tests of steamed sponge yellow pumpkin flour can be accepted by the public in terms of color, aroma, texture, and taste.